Une analyse des variations spatio-temporelles de l'exposition individuelle à la pollution de l'air en Île-de-France à partir de micro-capteurs - Nabil Touili; Katia Radja; Patrick Schembri; Ahmad Ktaish; Karine Zeitouni; Basile Chaix; Isabella Annesi-Maesano; Boris Dessimond; Jean-Marc Naude; Salim Srairi; Hafsa El-hafyani (Cybergeo, 2022)
Air quality is a major issue for urban policies, which implement regulatory monitoring devices and fine-scale modelling tools to monitor air pollution. Recently, mobile and connected devices have been used as a valuable tool in this regard, allowing more observations and real-time indicative data on individual exposure in all environments. In this article, individual exposure to the pollutants PM2.5, NO2 and Black Carbon (BC) is analysed based on geolocated and embedded micro-sensor observations from eighty-eight voluntary participants of two cohorts in Île-de-France. This data was complemented by interviews with eight of the cohorts’ participants and ten institutional stakeholders. Our findings reveal wide variations in exposure depending on the pollutant, on the microenvironment ("home", "work", "transport", "other places"), on the transport modes and on particular daily activities. In addition to commuting, this paper highlights additional exposure, particularly to PM2.5 during weekends, within and when travelling to the microenvironment "other places" that include indoor and outdoor leisure time spaces. Peaks of pollutant concentration during some individual travel by tram and bicycle are interpreted in their specific contexts. An analytical synthesis of all our results shows that mobility behavior and exposure intensity in some specific microenvironments require particular attention from an air quality perspective.